Feasibility study of high-power electron linac for clinical X-ray ROAD-FLASH therapy system - Kutsaev, Sergey V.; Agustsson, Ronald; Boucher, Salime; Carriere, Paul; Ghoniem, Nasr; Kaneta, Kenichi; Kravchenko, Maksim; Li, Alan; Moro, Adam; Patel, Sohun; Sheng, Ke (Frontiers in Medical Engineering, 2024)
Recent studies have demonstrated that the FLASH effect that allows to effectively kill tumor cells while sparing normal tissue occurs when large dose rates (≥40 Gy/s) are delivered in less than 1 s. This effect can be obtained either with hadrons, electrons, or photons. Photons are very attractive since modest energies of several MeV are needed, which can be achieved with compact and costefficient accelerators. However, since the efficiency of electron-to-photon conversion is only a few percent, the required beam intensity must be an order of magnitude higher than that state-of-the-art accelerators can provide. In response to this problem, our group has proposed the design of a linac, capable of accelerating 18 MeV 8 mA electron beam with further conversion to 100 Gy/s dose. The design is based on a traveling wave accelerating structure with high power efficiency, operating in a short-burst/long-pulse regime that allows operating power supply in a regime, beyond its specifications. In this paper, we will demonstrate the feasibility of a high-power linac for a clinical X-ray FLASH therapy system, using detailed analysis and simulations.